Family with Parents Abroad: New Challenge for Family Sociology - Juozeliūnienė, Irena; Kanapienė, Laura; Kazlauskaitė, Airina (Sociologija. Mintis ir veiksmas, 2008)
The article deals with new family structures as consequences of temporal migration of one or both parents abroad, while their children live in Lithuania alone, looked after by relatives, state institutions. The extent of this trend poses a challenge to family institution. The questions are raised whether these transnational family structures become an alternative to a nuclear family as was the case with cohabitation, commuting families, and LATs? What cognitive and emotional charge is contained within the public discourse of these families and how these new structures can be conceptualized in the academic field? The authors of the article seek to discuss the results of three sociological research studies, carried out from 2004 to 2006. Triangulation of methods and theoretical reflection of this new family form is presented. The data disclose the way families with parents abroad are portrayed in Lithuanian press and internet portal. Stigmatization and stigma management strategies experienced by children are reported. Theoretical reflection of new family form in terms of family stress and social exchange theories are discussed as well as explication of risk dimension and social networking are suggested.
Keywords: emigration; families with parents abroad; „abandoned children“; desolation; stigmatisation; stigma management